The Fight for Minds : Applying Strategic Communications to Achieve a Sectoral Transformation - Turilova, Kristina (World Bank, Washington, DC, 2012)
How can International Finance Corporation (IFC) advisory teams with limited numbers and budgets trigger actions among multiple players to bring about an impact that reaches the scale of a country or a sector? The IFC Russia Cleaner Production Program encountered that question when initiating a benchmarking study of the ferrous foundry sector in Russia. The author knew that no agent of change is more powerful than an idea. The key is to get the idea firmly planted in the hearts and minds of the participants, who then will act on it and achieve the desired impact. To engage the whole sector in converting to resource-efficiency practices, the author had to approach communications strategically. The objective: root the use of benchmarking in the minds of sector decision makers and engage multiple stakeholders the author did not have direct access to and convince them to participate in the study. This smart lesson outlines the three keys to effective strategic communications, which can apply to any Advisory Services (AS) program with a similarly ambitious target of changing the mindset of stakeholders.